A reply to Komárek - Alexander Somek; Elisabeth Paar (European Law Open)
This is a reply to Komárek’s criticism of our article “Europe’s political constitution”. We address the issues raised by our critic one by one. The topics range from the definition of the public sphere to the role that law blogs and social media play in it. The reply concludes by examining what it means to pursue truth in legal scholarship based on contrasting the views of Hans Kelsen und Stanley Fish.